LEARN2MOVE 0–2 years, a randomized early intervention trial for infants at very high risk of cerebral palsy: neuromotor, cognitive, and behavioral outcome. Issue 26 (17th December 2020) - Hielkema, Tjitske; Hamer, Elisa G.; Boxum, Anke G.; La Bastide-Van Gemert, Sacha; Dirks, Tineke; Reinders-Messelink, Heleen A.; Maathuis, Carel G. B.; Verheijden, Johannes; Geertzen, Jan H. B.; Hadders-Algra, Mijna; ,
Abstract: Purpose: Evidence for efficacy of early intervention in infants at high risk of cerebral palsy (CP) is limited. We compared outcome of infants at very high risk of CP after receiving the family centered program COPing with and CAring for infants with special needs (COPCA) or typical infant physiotherapy. Materials and methods: Forty-three infants were randomly assigned before the corrected age of 9 months to 1 year of COPCA ( n  = 23) or typical infant physiotherapy ( n  = 20). Neuromotor development, cognition, and behavior was assessed until 21 months corrected age. Video-recorded physiotherapy sessions were quantitatively analyzed for further process analyses. Outcome was evaluated with nonparametric tests and linear mixed effect models. Results: During and after the interventions, infant outcome in both intervention groups was similar [primary outcome Infant Motor Profile: COPCA 82 (69–94), typical infant physiotherapy 81 (69–89); Hodges Lehman estimate of the difference 0 (confidence interval −5;4)]. Outcome was not associated with contents of intervention. Conclusions: One year of COPCA and 1 year of typical infant physiotherapy in infants at high risk of CP resulted in similar neurodevelopmental outcomes. It is conceivable that combinations of active ingredients from different approaches are needed for effective early intervention. IMPLICATIONS FOR REHABILITATION: For infants at very high risk of cerebral palsy, 1 year of intervention with the family-centred programme Coping with and Caring for infants with special needs resulted in similar infant outcome as 1 year of typical infant physiotherapy. Infant's neuromotor, cognitive, and behavioural outcome was not associated with specific interventional elements, implying that the various elements may have a similar effect on developmental outcome. We suggest that a specific mix of ingredients of different approaches may work best, resulting in comprehensive care including both infant and family needs.